Ethical Implications of Usage of AI Models by Undergraduate Students in Academia - Do, Tuan; Kučera, Dušan; Kvítková, Zuzana; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This thesis aims to discuss and elaborate the ethical concerns that are brought to light in the use of artificial intelligence (AI) among undergraduate college students. This is presented through the description and analysis of decision-making processes and various ethical dilemmas that undergraduates regularly face while using AI models to assist with their academic work. AI refers to digital technologies or automated machines that can simulate diverse aspects of human intellect. Conversely, in an educational context, students use AI tools to serve various functions, such as writing, paraphrasing, and summarizing content. The most commonly used AI tools include generative AI tools, of which ChatGPT is the most popular and widely used tool by students for academic help. Even though these tools save much of the students' time and are convenient, their use comes with a variety of ethical dilemmas, such as infringing on academic integrity and honesty. To investigate these ethical implications, this thesis deployed a mixed-methods study. The study included a secondary qualitative case analysis of four case studies on AI usage in academia. These case studies were supplemented by a primary quantitative public survey that polled 58 participants (including 34 undergraduate exchange students) in the Czech Republic. The survey sought responses from the respondents concerning their use of AI tools and their awareness of the ethical consequences associated with their usage. The four case studies establish that AI usage is rampant among students as well as faculty, and this usage has been on an upward trend with the surge in the number of AI tools available online. The case studies also affirm that institutions are aware of student use of AI tools and have taken proactive policy steps to promote ethical and responsible use.
Some of the ethical issues of AI use identified include being a threat to academic integrity and honesty, exposure to biases of AI tools, and the possibility of adverse effects of AI overlapping into the job market. The findings confirmed that the use of AI is very rampant among students, with 91.18% of the respondents reporting that they have used AI in academics. Such usage, however, does not be necessarily aware of the ethical implications of the use of AI in academics. From these findings, the thesis states that the infusion of AI in academics is bound to happen and cannot practically be stopped. The best approach would be for institutions and other academic stakeholders to collectively devise ways of promoting ethical and responsible use of such tools, including appropriate documentation and acknowledgment where present.
Vedoucí práce: Dušan Kučera
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses